2021
DOI: 10.3389/fmicb.2021.673206
|View full text |Cite
|
Sign up to set email alerts
|

PDR Transporter ABC1 Is Involved in the Innate Azole Resistance of the Human Fungal Pathogen Fusarium keratoplasticum

Abstract: Fusarium keratoplasticum is arguably the most common Fusarium solani species complex (FSSC) species associated with human infections. Invasive fusariosis is a life-threatening fungal infection that is difficult to treat with conventional azole antifungals. Azole drug resistance is often caused by the increased expression of pleiotropic drug resistance (PDR) ATP-binding cassette (ABC) transporters of the ABCG sub-family. Most investigations of Fusarium ABC transporters associated with azole antifungal drug resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…It is quite likely that the rather distantly related isolate Fstr541 ( Figure 1 ) and possibly also the only voriconazole resistant F. falciforme isolate Ff0020, both of clinical origin, have different voriconazole resistance conferring mutations. One possibility may be gain of function mutations in a transcription factor that causes the overexpression of orthologs of the recently discovered multidrug efflux pump, F. keratoplasticum Abc1 [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is quite likely that the rather distantly related isolate Fstr541 ( Figure 1 ) and possibly also the only voriconazole resistant F. falciforme isolate Ff0020, both of clinical origin, have different voriconazole resistance conferring mutations. One possibility may be gain of function mutations in a transcription factor that causes the overexpression of orthologs of the recently discovered multidrug efflux pump, F. keratoplasticum Abc1 [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although antifungal clinical breakpoints have not yet been established for fusaria, epidemiological cut-off values have been defined using the CLSI method [ 7 ]. We have previously shown that exposure to high but sub-growth inhibitory concentrations of VRC (16 mg/L) caused increased expression of cyp51A [ 25 ] and the PDR transporter abc1 [ 46 ]. F. keratoplasticum strain 2781 was initially grown on potato dextrose agar, PDA (Merck & Co., Kenilworth, NJ, USA) at 28 °C for a week.…”
Section: Methodsmentioning
confidence: 99%
“…Most intriguingly, however, this association held true across species boundaries with all VRC-resistant FSSC isolates (i.e., 3 F. keratoplasticum and 6 F. suttonianum isolates) possessing the 23 bp cyp51A promoter deletion [ 25 ]. We also recently reported a 372-fold induction of the mRNA levels of the pleiotropic drug resistance (PDR) transporter abc1 in response to VRC exposure [ 46 ]. When abc1 was expressed in S. cerevisiae it conferred up to 1024-fold increased resistance towards a range of xenobiotics including azoles [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, we have developed and refined a yeast-based efflux pump expression system ( 9 , 11 , 19 22 ) that allows us to study fungal efflux pumps in great detail. The overexpression of functional efflux pumps in the genetically modified host S. cerevisiae AD1-8u - has many advantages, of which one is the ability to isolate naturally selected inhibitor-resistant efflux pump mutants.…”
Section: Introductionmentioning
confidence: 99%